Biomasa y mineralomasa subterránea del encinar de La Castanya, Montseny - Canadell J.; Rodá F. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Root systems from 36 holm oak (Quercus ilex L.) trees were excavated, at La Castanya, Biological Station, Montseny. Allometric equations were developed to estimate below ground biomass at an experimental plot. Because of fine root losses during excavation, 13 soils were used to asses fine root biomass. Thus, of the total tree biomass of 228,1 t/ha, 67,7 t/ha are accounted by root components (29,7 per cent): 32,7 t/ha by roots > 5 in diameter, 18,6 t/ha by roots 1 to 5 cm in diameter, and 16,4 t/ha by fine roots (diameter < 1 cm). Nutrient relative content of below ground biomass is 27,8 per cent N, 24,2 per cent P, 19,4 per cent Ca, 33,3 per cent K and 32,2 per cent Mg.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)